THE MOTIVATION AND ATTITUDE TOWARDS TOEFL SCORE OF NURSING STUDENTS PROGRAM STIKES NGUDIA HUSADA MADURA - Sitti Sulaihah; Dhaniel Prasetyo Irianto; Heni Ekawati (NHM PRESS, 2022)
Research conducted at STIKes Ngudia Husada Madura indicated that nursing students were still having problems with TOEFL preparation. Objective: This study aimed to further describe the motivation and attitudes of nursing students towards the TOEFL. Methods: Data were collected by administering the TOEFL test to nursing students at level three (the 6th semester) of the Nursing Science Study Program STIKes Ngudia Husada Madura, as well as a questionnaire measuring motivation and attitudes toward the TOEFL. Results: The results showed that although the respondents got a low score in the TOEFL test, they had high motivation and a supportive attitude towards TOEFL. Discussion: This illustrates that more innovative and effective methods are needed in learning English with the aim of increasing the English language skills of nursing students, especially at STIKes Ngudia Husada Madura.